Right sensory-motor functional networks subserve action observation therapy in aphasia. - Gili, Tommaso; Fiori, Valentina; De Pasquale, Giada; Sabatini, Umberto; Caltagirone, Carlo; Marangolo, Paola (Brain Imaging & Behavior, 2017)
Recent studies have shown that the systematic and repetitive observation of actions belonging to the experiential human motor repertoire without verbal facilitation enhances the recovery of verbs in non fluent aphasia. However, it is still an open question whether this approach extends its efficacy also on discourse productivity by improving the retrieval of other linguistic units (i.e. nouns, sentences, content words). Moreover, nothing is known regarding the neural substrates which support the language recovery process due to action observation treatment.In the present study, ten non fluent aphasics were presented with two videoclips (real everyday life context vs. familiar pantomimed context), each video for six consecutive weeks (Monday to Friday, weekend off). During the treatment, they were asked to observe each video and to describe it without verbal facilitation from the therapist. In all patients, language measures were collected before and at the end of treatment. Before and after each treatment condition (real vs. pantomimed context), each subject underwent a resting state fMRI. After the treatment, significant changes in functional connectivity were found in right sensory-motor networks which were accompanied by a significant improvement for the different linguistic units in the real context condition. On the contrary, the language recovery obtained in the pantomimed context did not match any functional modification. The evidence for a recruitment of the sensory-motor cortices during the observation of actions embedded in real context suggests to potentially enhance language recovery in non fluent aphasia through a simulation process related to the sensory-motor properties of actions.